EFEKTIVITAS MODEL DIRECT INTRUCTION TERHADAP KETERAMPILAN RENANG GAYA BEBAS PADA SISWA KELAS VIII DI SMPN 1 KARAWANG TIMUR - agung agung; Rekha Ratri Julianti (Jurnal Speed (Sport, Physical Education, Empowerment), 2020)
Teaching and learning activities at SMPN 1 East Karawang there is less effective learning in the delivery of material to students. One of them is aquatic learner swimming in freestyle, so it requires a suitable learning model in its implementation. In this research students find the difficulties to capture the delivered material by the teacher so students cannot follow the learning well. The purpose of this study was to determine the effectiveness of the direct instruction model on freestyle swimming skills. This study consisted of 360 students. The research sample of 60 students with random cluster sampling technique. Data collection in this study used the freestyle swimming test. Data were analyzed using 9.65 t-test compared with 2.042 t-table. The results of the study indicate that there is an effectiveness of the direct instruction model on freestyle swimming skills.